Activating Agency through Life Design - Tanja Vierrether; Anne Stone; Melissa Nelson (CERN IdeaSquare Journal of Experimental Innovation)
Institutions of higher education must support students in their learning for personal and professional development. Given this mission, colleges and universities work to deliver and evaluate the best educational models to students. This paper shares a case study about the potential of life design that incorporates the framework of the United Nations Sustainable Development Goals prototyped at a liberal arts institution in the United States of America. The case study outlines preliminary findings from a pre/post-test survey that measures perceived creativity, bias toward action, curiosity, problem reframing, and changemaking – key aspects of life design programming. Educators may develop their own programs and evaluation strategies based on this critical reflection.